Analysis of healthcare needs differences and influencing factors among elderly population: Evidence from Yangtze River Delta region, China - Chen Li; Jiaji Wu; Yang Li; Yi Huang (Frontiers Media S.A., 2022)
The quality of healthcare services is related to the quality of life of older people in their later years. A comprehensive evaluation of the healthcare needs of the elderly is the basic basis for providing targeted healthcare services for the elderly population. Taking the Yangtze River Delta region of China as an example, this article constructs an index system for evaluating the healthcare needs among the elderly, and explores the healthcare needs of the elderly and the influencing factors based on Dataset of the Fourth Sample Survey on the Living Conditions of China's Urban and Rural Older Persons. The study concludes that: Age 75 is the cut-off point for the healthcare needs of the elderly, with the growth of healthcare needs of the elderly aged 60-75 relatively flat and the growth of healthcare needs of the elderly aged 75 and above rising sharply. There is a wide variation in the Daily Activities Care Index, Incontinence Index and Aids Use Index scores and their indicators, as reflected in the differences in healthcare needs of older people in different age groups and in urban and rural areas. Healthcare needs of the elderly show a high positive correlation with the Daily Activities Care Index and Incontinence Index; healthcare needs of the elderly show a cubic function curve correlation with the assistive device use index. Community elderly healthcare services are conditions that influence the demand for elderly healthcare, but the low proportion of elderly people staying in elderly care institutions is due to a combination of low affordability, general quality of elderly care services and cultural factors. Educational attainment and marital status are micro-conditions that influence the demand for healthcare in old age. In terms of educational attainment, elderly people who have not attended school have an increasing need for healthcare as they get elderly. In terms of marriage, there is a strong negative correlation between the willingness to healthcare needs among elderly people with a spouse and a strong willingness to healthcare needs among elderly people who are widowed.